Problem Solving Profile of Grade VIII Students in Materials Linear Inquiry of One Variable Reviewed from the Level of Mathematic Anxiety in Palu GPID Christian School - Permana, Rio Arthur; Jaeng, Maxinus; Bennu, Sudarman (Universitas Tadulako, 2018)
The background of this study is that students in the SMP Kristen GPID Palu have different levels of mathematics anxiety, some are very fond of mathematics, but not a few are anxious and tend to be afraid of mathematics. This is an interest to study in order to obtain a problem-solving profile of students who has mild, moderate, and severe anxiety levels. The purpose of this study was to obtain a problem-solving profile of class VIII students on the material in a linear inequality with one variable that was viewed from the level of mathematics anxiety in SMP Kristen GPID Palu. The question that will be answered in this study is how the problem-solving profile of class VIII students on linear inequality with one variable in terms of mathematics anxiety level in SMP Kristen GPID Palu. The researcher conducted a qualitative descriptive study with a qualitative approach. Data was collected by giving an anxiety questionnaire according to HARS, problem-solving test, interviews, and field notes. The result of this study showed that students with mild anxiety levels were able to solve the problem that was given well, students with moderate anxiety levels were able to solve problems that were given quite well, students with severe anxiety levels were able to solve problems that were given poorly.